Scratching Below the Surface: Screening for Posttraumatic Stress Symptoms Following Hospitalization With the Pediatric Trauma Service. Issue 4 (July 2018) - Cline, Virginia Depp; Whitaker, Brian; Duran, Petra A.; Ratcliff, Kelly; Rosenfeld, Eric H.; Naik-Mathuria, Bindi
Abstract : Significant progress has occurred medically for children who have experienced traumatic injuries; however, attention to their psychological adjustment has only more recently been a focus in research and clinical practice. These needs do not cease at discharge but, instead, require monitoring to determine whether further assessment and/or intervention are required. Our team, inclusive of the Psychology Service and the Trauma Service, identified 2 established screening measures (based on age) that were completed by patients during their outpatient follow-up visits postdischarge. Should a patient screen positive, the Trauma Service referred them to the Psychology Service for further evaluation and possible treatment (i.e., trauma-focused cognitive-behavioral therapy). Of 881 trauma activations, 31 (4%) patients were screened at an outpatient follow-up appointment through pediatric surgery/trauma clinic. Of these completed screening tools, 29% screened positive and warranted a referral to Psychology. Intervention was recommended for the majority of the patients evaluated; however, half of these did not return for this intervention. A collaboration between the Psychology Service and the Trauma Service is a vital step toward providing stepped care for patients after unintentional injuries. This allows for evaluation of patient needs and then a referral source to meet these identified needs. Future directions include increasing the number of screened patients, perhaps with use of technological supports (i.e., REDCap) or expansion into other clinics and consideration of ways to increase family's use of psychological intervention. Level of Evidence: Therapeutic/Care management Level IV